Designing a Healthy Food Partnership: lessons from the Australian Food and Health Dialogue - Alexandra Jones; Roger Magnusson; Boyd Swinburn; Jacqui Webster; Amanda Wood; Gary Sacks; Bruce Neal (BMC, 2016)
Abstract Background Poor diets are a leading cause of disease burden worldwide. In Australia, the Federal Government established the Food and Health Dialogue (the Dialogue) in 2009 to address this issue, primarily through food reformulation. We evaluated the Dialogue's performance over its 6 years of operation and used these findings to develop recommendations for the success of the new Healthy Food Partnership. Methods We used information from the Dialogue website, media releases, communiqués, e-newsletters, materials released under freedom-of-information, and Parliamentary Hansard to evaluate the Dialogue's achievements from October 2013 to November 2015, using the RE-AIM (reach, efficacy, adoption, implementation and maintenance) framework. We also engaged closely with two former Dialogue members. Our findings update a prior assessment done in October 2013. Results Little data is available to evaluate the Dialogue's recent achievements, with no information about progress against milestones released since October 2013. In the last 2 years, only one additional set of sodium reduction targets (cheese) was agreed and Quick Service Restaurant foods were added as an area for action. Some activity was identified in 12 of a possible 137 (9 %) areas of action within the Dialogue's mandate. Independent evaluation found targets were partially achieved in some food categories, with substantial variation in success between companies. No effects on the knowledge, behaviours or nutrient intake of the Australian population or evidence of impact on diet-related disease could be identified. Conclusions The new Healthy Food Partnership has similar goals to the Dialogue. While highly laudable and recognised globally as cost-effective, the mechanism for delivery in Australia has been woefully inadequate. Strong government leadership, adequate funding, clear targets and timelines, management of conflict of interest, comprehensive monitoring and evaluation, and a plan for responsive regulation in the event of missed milestones will be required if the new Healthy Food Partnership is to achieve its urgent public health goals.